2022
DOI: 10.1002/acm2.13561
|View full text |Cite
|
Sign up to set email alerts
|

HyperArc VMAT stereotactic radiotherapy for locally recurrent previously‐irradiated head and neck cancers: Plan quality, treatment delivery accuracy, and efficiency

Abstract: This paper demonstrates the clinical feasibility and efficacy of Hyper-Arc VMAT treatments for locally recurrent, locally advanced, or previously irradiated head and neck cancers treated with stereotactic radiotherapy (SRT). Materials/Methods: First, an anthropomorphic SRS head phantom from the MD Anderson's IROC credentialing laboratory containing a 1.9 cm diameter spherical target, including in vivo dosimetry system, was imaged, planned, and irradiated (25 Gy in 1 fraction) using HyperArc VMAT with a 6 MV fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…For head and neck cancers, HA has been demonstrated to be an effective treatment with a highly conformal dose distribution and excellent OAR sparing. Additionally, radiation therapists did not need to enter the treatment room to rotate the treatment couch even in the noncoplanar beam arrangement (16,25,26).…”
Section: Comparison Of the Beam Arrangement And Dose Distribution Bet...mentioning
confidence: 99%
See 1 more Smart Citation
“…For head and neck cancers, HA has been demonstrated to be an effective treatment with a highly conformal dose distribution and excellent OAR sparing. Additionally, radiation therapists did not need to enter the treatment room to rotate the treatment couch even in the noncoplanar beam arrangement (16,25,26).…”
Section: Comparison Of the Beam Arrangement And Dose Distribution Bet...mentioning
confidence: 99%
“…A number of investigators have reported that HA plans provided a higher conformity dose for the target and a lower radiation dose for surrounding tissues compared to VMAT plans for patients with brain metastases (14). Recently, HA has been applied to extracranial tumors, such as angiosarcoma of the scalp (15) and head and neck cancers (16,17). Its superior dose distribution could form a new treatment approach.…”
mentioning
confidence: 99%
“…Avoiding collisions between the patient's body and the gantry during external radiation therapy is important. Newer treatment planning software (TPS) for x‐ray stereotactic radiotherapy can simulate treatment device parameters, such as the gantry and couch angles, while avoiding collisions 1 . This function benefits proton therapy, where a snout is placed close to patients to optimize the therapeutic dose distribution 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Newer treatment planning software (TPS) for x-ray stereotactic radiotherapy can simulate treatment device parameters, such as the gantry and couch angles, while avoiding collisions. 1 This function benefits proton therapy, where a snout is placed close to patients to optimize the therapeutic dose distribution. 2 Unfortunately, TPSs cannot check the collision outside the computed tomography (CT) imaging range because they only handle F I G U R E 1 Difference between the proposed and the previous method.…”
Section: Introductionmentioning
confidence: 99%
“…This automated system has made simultaneous treatment of multiple brain tumors more accessible with efficiency gains in both plan preparation and treatment delivery. [1][2][3] However, unlike single isocenter plans with a single target, Single Isocenter Multiple Targets (SIMT) plans are sensitive to rotational set-up errors. [4][5][6][7][8] In their retrospective study using patient data treated with HyperArc, Sagawa et al 9 investigated the dosimetric impact of setup errors on plans with both single and multiple brain metastases.…”
Section: Introductionmentioning
confidence: 99%